Preparation method of hollow SiO2 nanoparticles with adjustable morphology and SiO2 film
The sol-gel method uses raw materials such as polyacrylic acid and polydimethylsiloxane to prepare adjustable hollow SiO2 nanoparticles, which solves the problem of preparing porous SiO2 nanoparticles in the prior art, and achieves adjustable refractive index and high transmittance of SiO2 films.
Patent Information
- Application Number
- CN202510063503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art is difficult to prepare porous SiO2 nanoparticles of different morphology under mild conditions, and the traditional methods have problems such as high equipment cost, complex operation, and difficult to regulate refractive index and film thickness, which limits the application of large-area preparation and ultra-low refractive index materials.
Polyacrylic acid was used as the template agent, polydimethylsiloxane and ethyl orthosilicate were used as raw materials by the sol-gel method, and the volume ratios of the two were changed to prepare hollow SiO2 nanoparticles with controllable morphology.
The preparation of hollow SiO2 nanoparticles with adjustable morphology under mild conditions was achieved. By changing the morphology of the nanoparticles, it provides a new idea for preparing ultra-low refractive index materials, and significantly improves the transmittance of SiO2 films to specific wavelength light.
Smart Images

Figure CN119898772A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical films and nano materials, and more specifically, the invention relates to a method for preparing hollow SiO2 nanoparticles with adjustable morphology and a SiO2 film. Background Art
[0002] Porous optical films have broad application prospects in sensors, microelectronics, etc. due to their advantages of high specific surface area, low dielectric constant and adjustable refractive index. SiO2 has low refractive index, low dielectric constant, chemical inertness and thermal stability, which makes the application of SiO2-based films in optics and electronics widely concerned. Although SiO2 (refractive index n is 1.46) is already one of the low refractive index dense materials, the practical application of optical performance devices usually requires a lower refractive index of the material, which has prompted the research of ultra-low refractive index porous SiO2 films with different morphologies. When pores are introduced into the film, the refractive index value of the SiO2 film will decrease, but it is still far from the refractive index of air (1.0). Therefore, it is necessary to study different methods to prepare low refractive index SiO2 materials. Among them, chemical etching and high-temperature calcination of templates are effective methods to obtain porous SiO2 materials, but the etchant is toxic and harmful, which is not conducive to large-scale production and application, and high-temperature calcination will damage the precision optical substrate. In addition, the oblique angle deposition method can be used to prepare SiO2 nanorod array films, but this method has high equipment cost, complex operation, and the refractive index and film thickness are not easy to control. It is also not suitable for large-scale preparation. Therefore, it is necessary to develop a method for preparing porous SiO2 nanoparticles with different morphologies under mild conditions, and then use it to prepare porous SiO2 films with adjustable refractive index. Summary of the invention
[0003] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0004] In order to achieve these purposes and other advantages according to the present invention, a method for preparing hollow SiO2 nanoparticles with adjustable morphology is provided, comprising: using polyacrylic acid as a template, polydimethylsiloxane and tetraethyl orthosilicate as raw materials, preparing hollow SiO2 nanoparticle sol by a sol-gel method, and synthesizing hollow SiO2 nanoparticles with controllable morphology by changing the volume ratio of polydimethylsiloxane and tetraethyl orthosilicate.
[0005] Preferably, the method specifically comprises the following steps:
[0006] Step 1: dissolving a certain amount of polyacrylic acid in ammonia water at room temperature, and then adding anhydrous ethanol to mix and stir to obtain solution A;
[0007] Step 2: adding a certain amount of polydimethylsiloxane to the solution A in step 1 under a certain temperature condition to obtain a mixed solution;
[0008] Step 3, dividing a certain amount of ethyl orthosilicate into 5 equal parts, and gradually adding the parts into the mixed solution obtained in step 2 at a certain time interval to obtain solution B;
[0009] Step 4: Stir the solution B in step 3 at a certain temperature until a sol is formed, and then age it;
[0010] Step 5: Filter the aged sol to obtain hollow SiO2 nanoparticles.
[0011] Preferably, in the step 1, the mass volume ratio of polyacrylic acid, aqueous ammonia and anhydrous ethanol is 0.10-20 g: 5-15 mL: 150-200 mL.
[0012] Preferably, in the step 2, the temperature of solution A is 30° C. when polydimethylsiloxane is added, and the volume ratio of polydimethylsiloxane to ammonia water is 0-1:5-15.
[0013] Preferably, in step three, the time interval is 1 hour.
[0014] Preferably, in step three, the volume ratio of polydimethylsiloxane to tetraethyl orthosilicate is 1:0-3.
[0015] Preferably, in step 4, the stirring temperature of solution B is 40-60° C., and the stirring time is 36-72 h.
[0016] Preferably, in step five, the filter paper used for filtration is 0.22 μm pore size PVDF filter paper.
[0017] A SO2 film is prepared from the above-mentioned hollow SiO2 nanoparticles with adjustable morphology.
[0018] A method for preparing an SO2 film comprises: cleaning a substrate with a plasma cleaner, immersing the substrate in a hollow SiO2 nanoparticle sol for 20 to 40 seconds at a speed of 200 to 600 mm / min using a pull-up coating machine, and coating a SiO2 film.
[0019] In order to improve the transmittance of the SO2 film to light with a wavelength of 800 to 900 nm, an equal amount of modified polydimethylsiloxane is used to replace the polydimethylsiloxane in step 1, wherein the preparation method of the modified polydimethylsiloxane comprises:
[0020] Add polydimethylsiloxane, diphenylsilanediol and tridecafluorooctyltriethoxysilane into a reaction kettle, add 0.05 mol / L potassium hydroxide solution, stir and mix evenly, heat to 100-120°C, stir and react for 12-18 hours at a stirring speed of 300-500 rpm. After the reaction is completed, wash with water to remove the potassium hydroxide solution to obtain modified polydimethylsiloxane; wherein the volume ratio of polydimethylsiloxane, diphenylsilanediol, tridecafluorooctyltriethoxysilane and potassium hydroxide solution is 4:1-2:1:2-4.
[0021] The present invention at least includes the following beneficial effects: the present invention uses polyacrylic acid (PAA) as a template, prepares hollow SiO2 nanoparticle (HSNs) sol by a sol-gel method, and can synthesize morphology-controllable hollow SiO2 nanoparticles by changing the volume ratio of polydimethylsiloxane (PDMS) and tetraethyl orthosilicate (TEOS), and the morphology of the hollow nanoparticles includes spherical shape and tadpole shape. The present invention adjusts the refractive index by changing the morphology of the nanoparticles, thereby providing a new idea for preparing ultra-low refractive index materials.
[0022] The SiO2 film prepared using the hollow SiO2 nanoparticles of the present invention has a high transmittance to 300-900nm light, but the peak transmittance is concentrated at 350-400nm; after the hollow SiO2 nanoparticles are prepared using polydimethylsiloxane modified with diphenylsilanediol and tridecafluorooctyltriethoxysilane, the transmittance of the SiO2 film to 800-900nm light is significantly improved.
[0023] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 TEM image of the SiO2 film prepared in Example 1;
[0025] Figure 2 TEM image of the SiO2 film prepared in Example 2;
[0026] Figure 3 TEM image of the SiO2 film prepared in Comparative Example 1;
[0027] Figure 4 The transmittance variation curves of the SiO2 films prepared in the blank substrate, Example 1, Example 2 and Comparative Example 1 to light of different wavelengths. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0029] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0030] Example 1
[0031] This embodiment provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology, comprising the following steps:
[0032] Step 1: Dissolve 0.15 g of polyacrylic acid (PAA) in 7 mL of aqueous ammonia at 25° C., then add 180 mL of anhydrous ethanol and mix and stir to obtain solution A;
[0033] Step 2: Add 0.5 mL of polydimethylsiloxane to solution A at 30° C. to obtain a mixed solution;
[0034] Step 3, divide 1 mL of ethyl orthosilicate into 5 equal parts, and gradually add the parts into the mixed solution 5 times at intervals of 1 hour to obtain solution B;
[0035] Step 4: Stir the solution B in step 3 at 50° C. for 48 h until a sol is formed and age the solution;
[0036] Step 5: Filter the aged sol using 0.22 μm pore size PVDF filter paper to finally obtain hollow SiO2 nanoparticles with adjustable morphology.
[0037] The method for preparing SiO2 film using the hollow SiO2 nanoparticles of this embodiment is: clean the substrate with a plasma cleaner, immerse the substrate in the hollow SiO2 nanoparticle sol at a speed of 500mm / min for 30s using a pulling coating machine, and coat the SiO2 film. The refractive index of the SiO2 film is 1.11.
[0038] Example 2
[0039] This embodiment provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology, comprising the following steps:
[0040] Step 1: Dissolve 0.15 g PAA in 7 mL ammonia water at 25°C, then add 180 mL anhydrous ethanol and mix and stir to obtain solution A;
[0041] Step 2: Add 1 mL of polydimethylsiloxane to the solution A in step 1 at 30° C. to obtain a mixed solution;
[0042] Step 3: Divide 1 mL of ethyl orthosilicate into 5 equal parts, and gradually add the parts into the mixed solution of step 2 5 times at intervals of 1 hour to obtain solution B;
[0043] Step 4: Stir the solution B in step 3 at 50° C. for 48 h until a sol is formed and age the solution;
[0044] Step 5: Filter the aged sol using 0.22 μm pore size PVDF filter paper to finally obtain hollow SiO2 nanoparticles with adjustable morphology.
[0045] The method for preparing SiO2 film using the hollow SiO2 nanoparticles of this embodiment is: clean the substrate with a plasma cleaner, immerse the substrate in the hollow SiO2 nanoparticle sol at a speed of 500mm / min for 30s using a pulling coating machine, and coat the SiO2 film. The refractive index of the SiO2 film is 1.08.
[0046] Example 3
[0047] This embodiment provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology. The difference from Example 1 is that 0.5 mL of modified polydimethylsiloxane is used to replace the polydimethylsiloxane in Example 1. The methods and parameters of the remaining steps of this embodiment are the same as those of Example 1. The modification method of the modified polydimethylsiloxane includes:
[0048] 8 mL of polydimethylsiloxane, 2 mL of diphenylsilanediol, and 2 mL of tridecafluorooctyltriethoxysilane were added to a reaction kettle, and 5 mL of 0.05 mol / L potassium hydroxide solution was added. After stirring and mixing evenly, the mixture was heated to 120°C and stirred for 12 hours at a stirring speed of 400 rpm. After the reaction was completed, the potassium hydroxide solution was removed by washing with water to obtain modified polydimethylsiloxane.
[0049] The method for preparing SiO2 film using the hollow SiO2 nanoparticles of this embodiment is: clean the substrate with a plasma cleaner, immerse the substrate in the hollow SiO2 nanoparticle sol at a speed of 500mm / min for 30s using a pulling coating machine, and coat the SiO2 film. The refractive index of the SiO2 film is 1.07.
[0050] Example 4
[0051] This embodiment provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology. The difference between this embodiment and embodiment 2 is that 0.5 mL of modified polydimethylsiloxane is used to replace the polydimethylsiloxane in embodiment 2. The methods and parameters of the remaining steps of this embodiment are the same as those of embodiment 2.
[0052] 8 mL of polydimethylsiloxane, 3 mL of diphenylsilanediol, and 2 mL of tridecafluorooctyltriethoxysilane were added to a reaction kettle, and 6 mL of 0.05 mol / L potassium hydroxide solution was added. After stirring and mixing evenly, the mixture was heated to 120°C and stirred for 16 hours at a stirring speed of 500 rpm. After the reaction was completed, the potassium hydroxide solution was removed by washing with water to obtain modified polydimethylsiloxane.
[0053] The method for preparing SiO2 film using the hollow SiO2 nanoparticles of this embodiment is: clean the substrate with a plasma cleaner, immerse the substrate in the hollow SiO2 nanoparticle sol at a speed of 500mm / min for 30s using a pulling coating machine, and coat the SiO2 film. The refractive index of the SiO2 film is 1.05.
[0054] Comparative Example 1
[0055] This comparative example provides a method for preparing hollow SiO2 nanoparticles, comprising the following steps:
[0056] Step 1: Dissolve 0.15 g of polyacrylic acid (PAA) in 7 mL of aqueous ammonia at 25° C., then add 180 mL of anhydrous ethanol and mix and stir to obtain a solution;
[0057] Step 2: Divide 1 mL of tetraethyl orthosilicate (TEOS) into 5 equal parts and gradually add them into the solution 5 times at intervals of 1 hour;
[0058] Step 3: Stir the solution of step 2 at 50° C. for 48 hours until a sol is formed and age it;
[0059] Step 4: Filter the sol obtained in step 3 using 0.22 μm pore size PVDF filter paper to finally obtain hollow SiO2 nanoparticles with adjustable morphology.
[0060] The method for preparing SiO2 film using the hollow SiO2 nanoparticles of this comparative example is: cleaning the substrate with a plasma cleaner, immersing the substrate in the hollow SiO2 nanoparticle sol at a speed of 500 mm / min for 30 seconds using a pulling coating machine, and coating a SiO2 film with a refractive index of 1.15.
[0061] like Figure 1-Figure 3 As shown, by changing the value of PDMS / TEOS, three kinds of SiO2 nanoparticles with completely different morphologies were obtained in Example 1, Example 2 and Comparative Example 1, including nanotadpoles and hollow nanospheres with different hollowness. In Comparative Example 1, when PDMS / TEOS=0, only hollow SiO2 nanospheres were obtained, such as Figure 3When the PDMS / TEOS value increases, the resulting hollow silica nanoparticles (HSNs) are composed of hollow nanospheres and hollow nanotadpoles, as shown in Figure 1 As shown in the figure, more than 60% of the nanoparticles have a tadpole-like morphology. The hollow nanotadpole has a relatively round shape at one end, which constitutes the tadpole's head, and the hollow structure tapers at the other end, forming the tadpole's tail. The thickness of the SiO2 shell on the head and tail of the nanotadpole is relatively uniform, with a thickness of several nanometers. Figure 2 As shown in the figure, as the PDMS / TEOS value increases further, a rather strange phenomenon occurs: the hollow SiO2 nanotadpoles are covered by a layer of dark gray material, which is a hybrid of PDMS and SiO2. The different morphologies of the nanoparticles may be related to the deformation of the PAA clusters in the ethanol solution. From the above results, it can be seen that the PDMS concentration will directly affect the morphology of the final SiO2 nanoparticles.
[0062] Comparative Example 2
[0063] This comparative example provides a method for preparing hollow SiO2 nanoparticles, comprising the following steps:
[0064] Step 1: At room temperature, 0.04 g of PAA was dissolved in 7 mL of ammonia water to obtain a PAA ammonia solution; then 180 mL of ethanol and the PAA ammonia solution were mixed in a 250 mL conical flask to obtain a reaction solution;
[0065] Step 2: Then 1 mL of TEOS was divided into five equal parts and added into the vigorously stirred reaction solution in five portions, with a time interval of one hour.
[0066] Step 3: After the reaction is carried out for 48 hours, a hollow SiO2 nanoparticle sol is prepared.
[0067] The method for preparing SiO2 film from hollow SiO2 nanoparticles in this comparative example is:
[0068] First, the substrate was immersed in Piranha solution for 1 hour, and then placed in a saturated HDMS atmosphere for 24 hours. Finally, the film was prepared by a Czochralski coating method at a pulling speed of 1000 mm / min.
[0069] In this comparative example, hollow SiO2 nanoparticles (hollow SiO2 nanospheres and worm-like hollow SiO2 nanotubes) were successfully synthesized, and the refractive index of the SiO2 film was found to be 1.28.
[0070] Comparative Example 3
[0071] This comparative example provides a method for preparing hollow SiO2 nanoparticles. Compared with comparative example 2, the difference is that the amount of PAA used in step 1 of this comparative example is 0.08 g, and the methods and parameters of the remaining steps of this comparative example are the same as those of comparative example 2.
[0072] The hollow SiO2 nanoparticles prepared in this comparative example were prepared into a SiO2 film by the same preparation method as that in comparative example 1. The refractive index of the prepared SiO2 film was measured to be 1.19.
[0073] Comparative Example 4
[0074] This comparative example provides a method for preparing hollow SiO2 nanoparticles. Compared with comparative example 2, the difference is that the amount of PAA used in step 1 of this comparative example is 0.15 g, and the methods and parameters of the remaining steps of this comparative example are the same as those of comparative example 2.
[0075] The hollow SiO2 nanoparticles prepared in this comparative example were prepared into a SiO2 film by the same preparation method as that of comparative example 2. The refractive index of the prepared SiO2 film was measured to be 1.12.
[0076] Comparative Example 5
[0077] This comparative example provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology, which mainly includes the synthesis of solid SiO2 nanoparticles and their conversion into hollow SiO2 nanoparticles, specifically including the following steps:
[0078] Step 1: 10 mL of TEOS, 80 g of anhydrous ethanol and 6 g of aqueous ammonia were mixed and stirred at 22° C. for 8 h to obtain a solution;
[0079] Step 2: Static aging the solution in a sealed glass container at 22° C. for 3 days until a white sol containing solid SiO2 nanoparticles is obtained;
[0080] Step 3: Take 5 g of the white sol containing solid SiO2 nanoparticles obtained in step 2, add 100 g of a solution having a mass ratio of water to ethanol of 1:1 and store for 7 days. Collect the obtained hollow SiO2 nanoparticles by triple centrifugation, and then redisperse them in ethanol to obtain a hollow SiO2 nanoparticle sol.
[0081] The method for preparing SiO2 film from hollow SiO2 nanoparticles of this comparative example is as follows:
[0082] The substrate was immersed in a 0.1 wt% HF solution for 5 minutes, then rinsed with deionized water, and vertically immersed in the solution for 5 minutes using a pull-up coater, and then lifted from the solution at a given speed, and dried in air for 20 minutes.
[0083] In this comparative example, hollow SiO2 nanoparticles with different morphologies were successfully synthesized, and the refractive index of the SiO2 film was found to be 1.27.
[0084] Comparative Example 6
[0085] This comparative example provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology. Compared with comparative example 4, the difference is that the storage time of the white sol containing solid SiO2 nanoparticles in the mixed solution of water and ethanol in step three is 14 days. The methods and parameters of the remaining steps of this comparative example are the same as those of comparative example 5.
[0086] The refractive index of the SiO2 film prepared in this comparative example is 1.16.
[0087] Comparative Example 7
[0088] This comparative example provides a method for preparing hollow SiO2 nanoparticles with adjustable morphology, and PVP-functionalized monodisperse PS microspheres are prepared by PVP-mediated surfactant-free emulsion polymercuration, and the specific steps include:
[0089] Step 1: 10 g of styrene, 3.5 g of polyvinylpyrrolidone (PVP), 0.41 g of α-azobisisobutylaminopyridine dihydrochloride and 100 ml of deionized water were placed in a 250 ml round-bottom flask equipped with a nitrogen inlet, a condenser and a mechanical stirrer.
[0090] Step 2: The reaction solution was degassed with nitrogen for 60 min, then immersed in a 70° C. water bath and stirred at 300 rpm for 24 h.
[0091] Step 3: Collect the prepared PS microspheres by centrifugation, wash them three times with ethanol, and finally disperse them in ethanol for next use.
[0092] Step 4: Dissolve 1.31 g of hexadecyltrimethylammonium bromide (CTAB) in 40 mL of anhydrous ethanol, then add TEOS (0.8 mL to 4.8 mL), and disperse the mixture by ultrasonic oscillation for 30 minutes.
[0093] Step 5: Take 5 g of the PS microsphere ethanol dispersion prepared in step 3 and add it to the mixture prepared in step 4, and then stir for 10 min.
[0094] Step 6. Finally, add 1 ml of ammonia water to the reaction mixture and stir vigorously at 300 rpm for 3 h at 50 °C. Collect the PS / SiO2 microspheres by centrifugation and wash them three times with water and ethanol to remove the residual TEOS and ammonia water to obtain hollow SiO2 nanoparticle sol.
[0095] The method for preparing SiO2 film from hollow SiO2 nanoparticles in this comparative example:
[0096] The substrate was immersed in a 0.1% hydrofluoric acid solution for 5 min, and the substrate was lifted from the sol at a speed of 200 mm / min using a pull-up coater, and then calcined in air at 550°C for 6 h to remove the PS template of the PS / SiO2 microspheres to obtain a hollow SiO2 film.
[0097] This comparative example successfully synthesized hollow SiO2 nanoparticles with different morphologies by changing the TEOS content (0.8mL to 4.8mL), and found that the refractive index of the SiO2 film varied from 1.17 to 1.29.
[0098] The transmittance data of the blank substrate (glass sheet), the SiO2 films prepared in Example 1, Example 2 and Comparative Example 1 to light of different wavelengths were measured respectively, and the results were obtained. Figure 4 ,from Figure 4 It can be seen that within the wavelength range of 300-900nm, the transmittance of the SiO2 films prepared in Example 1, Example 2 and Comparative Example 1 to light within the wavelength range of 300-900nm is much higher than that of the blank substrate, among which, the transmittance of the SiO2 films prepared in Example 1 and Example 2 to light within the wavelength range of 300-900nm is significantly higher than that of Comparative Example 1, and the transmittance of the three SiO2 films to light within the wavelength range of 350-400nm is the highest; among which, the peak transmittance of the SiO2 film prepared in Example 1 reaches 98%, and the peak transmittance of the SiO2 film prepared in Example 2 reaches 98%. The peak transmittance of the film is 97.2%, both of which are higher than the 96.4% of the comparative example. However, the transmittance for light in the range of 800-900nm is not ideal. For the transmittance of light in the range of 800-900nm, the SiO2 film prepared in Example 1 is reduced to 93.3% at the lowest, and Example 2 is reduced to 94%, and the comparative example 1 is reduced to 93.2%; Examples 3 and 4 use SiO2 films prepared with modified polydimethylsiloxane, and their minimum transmittances for light in the range of 800-900nm reach 98.3% and 98.6%, respectively, which are significantly better than Examples 1 and 2.
[0099] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0100] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing hollow SiO2 nanoparticles with adjustable morphology, characterized in that: include: Hollow SiO2 nanoparticle sol was prepared by sol-gel method using polyacrylic acid as template and polydimethylsiloxane and tetraethyl orthosilicate as raw materials. Hollow SiO2 nanoparticles with controllable morphology were synthesized by changing the volume ratio of polydimethylsiloxane and tetraethyl orthosilicate.
2. The method for preparing hollow SiO2 nanoparticles with adjustable morphology according to claim 1, characterized in that: The specific steps include: Step 1: dissolving a certain amount of polyacrylic acid in ammonia water at room temperature, and then adding anhydrous ethanol to mix and stir to obtain solution A; Step 2: adding a certain amount of polydimethylsiloxane to the solution A in step 1 under a certain temperature condition to obtain a mixed solution; Step 3, dividing a certain amount of ethyl orthosilicate into 5 equal parts, and gradually adding the parts into the mixed solution obtained in step 2 at a certain time interval to obtain solution B; Step 4: Stir the solution B in step 3 at a certain temperature until a sol is formed, and then age it; Step 5: Filter the aged sol to obtain hollow SiO2 nanoparticles.
3. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 1, the mass volume ratio of polyacrylic acid, ammonia water and anhydrous ethanol is 0.10-20 g: 5-15 mL: 150-200 mL.
4. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 2, the temperature of solution A is 30° C. when polydimethylsiloxane is added, and the volume ratio of polydimethylsiloxane to ammonia water is 0-1:5-15.
5. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 3, the time interval is 1 hour.
6. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 3, the volume ratio of polydimethylsiloxane to tetraethyl orthosilicate is 1:0-3.
7. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 4, the stirring temperature of solution B is 40-60° C., and the stirring time is 36-72 hours.
8. The method for preparing hollow SiO2 nanoparticles with adjustable morphology as claimed in claim 2, characterized in that: In the step 5, the filter paper used for filtration is 0.22 μm pore size PVDF filter paper.
9. A SO2 film, characterized in that: The SO2 film is prepared from the morphology-adjustable hollow SiO2 nanoparticles described in any one of claims 1-8.
10. A method for preparing a SO2 thin film as claimed in claim 9, characterized in that: include: The substrate is cleaned with a plasma cleaner, and the substrate is immersed in the hollow SiO2 nanoparticle sol for 20 to 40 seconds at a speed of 200 to 600 mm / min using a pull-up coating machine to coat a SiO2 film.
Citation Information
Patent Citations
Composition comprising microcapsules containing particles with a high wet point
CN106572960A
Siloxane toughened and modified SiO2 aerogel and preparation method thereof
CN108117082A
Method for preparing high-hardness antireflection film on basis of hollow silicon dioxide
CN109502987A
Hydrophobic modified phosphate, preparation method thereof and application thereof to fireproof putty
CN109880425A
Functionalized silicon nanoparticles, composite materials including them, and preparation and uses thereof
US20250006933A1